2023
DOI: 10.3389/fgene.2023.1125970
|View full text |Cite
|
Sign up to set email alerts
|

Potential predictive value of circulating tumor DNA (ctDNA) mutations for the efficacy of immune checkpoint inhibitors in advanced triple-negative breast cancer

Abstract: Background: In recent years, tumor immunotherapy has become a viable treatment option for triple negative breast cancer (TNBC). Among these, immune checkpoint inhibitors (ICIs) have demonstrated good efficacy in advanced TNBC patients with programmed death-ligand 1 (PD-L1) positive expression. However, only 63% of PD-L1-positive individuals showed any benefit from ICIs. Therefore, finding new predictive biomarkers will aid in identifying patients who are likely to benefit from ICIs. In this study, we used liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…47,48 Tan et al found that immune checkpoint inhibitors (ICIs) efficacy in patients with advanced triple-negative breast cancer (TNBC) may be predicted by 12 mutant ctDNA genes, including SESN1. 49 Balázs et al found that radiotherapy accentuated the immune suppression of head and neck cancer patients via changing regulatory T cells and CTLA4 and PD-1 expression on CD4 cells in the peripheral blood, and expression of the FXDR, SESN1, GADD45, DDB2, and MDM2 were altered in the peripheral blood cells of patients after radiotherapy. 50 In the present study, KEGG enrichment analysis of the RNA-seq data showed that PD-L1 expression and PD-1 checkpoint pathway in cancer was enriched in the four NB cell lines transfected with SESN1 siRNA #1 and siRNA #2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 Tan et al found that immune checkpoint inhibitors (ICIs) efficacy in patients with advanced triple-negative breast cancer (TNBC) may be predicted by 12 mutant ctDNA genes, including SESN1. 49 Balázs et al found that radiotherapy accentuated the immune suppression of head and neck cancer patients via changing regulatory T cells and CTLA4 and PD-1 expression on CD4 cells in the peripheral blood, and expression of the FXDR, SESN1, GADD45, DDB2, and MDM2 were altered in the peripheral blood cells of patients after radiotherapy. 50 In the present study, KEGG enrichment analysis of the RNA-seq data showed that PD-L1 expression and PD-1 checkpoint pathway in cancer was enriched in the four NB cell lines transfected with SESN1 siRNA #1 and siRNA #2.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al. found that immune checkpoint inhibitors (ICIs) efficacy in patients with advanced triple‐negative breast cancer (TNBC) may be predicted by 12 mutant ctDNA genes, including SESN1 49 . Balázs et al.…”
Section: Discussionmentioning
confidence: 99%
“…TILs are mononuclear IC that infiltrate tumor tissue and are present in most types of solid tumors. TILs can be categorized into interstitial (sTIL) and intratumor TILs (iTIL) based on hematoxylin and eosin (H&E) staining ( 55 ). Compared to HR+ and HER2 positive breast cancers, triple-negative breast cancer (TNBC) has a higher level of TILs (20%) ( 56 ).…”
Section: Prognostic and Predictive Value Of Biomarkers Related To Ici...mentioning
confidence: 99%
“…Tan et al [68] investigated the genomic landscape underlying the response to ICPI treatment. To this end, they performed an Illumina assay of 457 cancer-related genes on plasma samples from 11 ICPI-treated TNBC patients.…”
Section: Ngs Analysis Of Markers For Tnbcmentioning
confidence: 99%